Effects of Reynolds and Prandtl Number on Mixed Convection in an Octagonal Channel with a Heat-Generating Hollow Cylinder - Parvin, S.; Nasrin, R. (Journal of Scientific Research, 2012)
A numerical study has been executed to analyze the effects of Reynolds and Prandtl number on mixed convective flow and heat transfer characteristics inside an octagonal vertical channel in presence of a heat-generating hollow circular cylinder placed at the centre. All the walls of the octagon are considered to be adiabatic. Galerkin weighted residual finite element method is used to solve the governing equations of mass, momentum and energy. Results are presented in terms of streamlines, isotherms, the average Nusselt number and the maximum fluid temperature for different combinations of controlling parameters namely, Reynolds number, Prandtl number and Richardson number. The results indicate that the flow and thermal fields as well as the heat transfer rate and the maximum fluid temperature in the octagonal channel depend significantly on the mentioned parameters. Keywords: Heat-generation; Hollow cylinder; Octagonal channel; Mixed convection; Finite element method. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i2.8142 J. Sci. Res. 4 (2), 337-348 (2012)